ظاهرة انتشار الطلاق "أسبابها، علاجها" في ضوء السنة النبوية - سلام، أحمد حمدي محمد (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بكفر الشيخ, 2020)
إن انتشار الطلاق من الظواهر الخطيرة التي ظهرت في عصرنا الحاضر، والتي تهدد الأسر والمجتمعات، وقد كان للسنة النبوية السهم الكبير في التصدي لأسباب الطلاق، ومعالجة مشكلاته. والناظر في السنة النبوية يجد أن الأصل في الحياة الزوجية منع الطلاق، وكراهته إلا لضرورة قصوى، وسبب وجيه، كفقد الباءة، وسوء العشرة، والعقم، ونحو ذلك، وقد عالجت السنة النبوية كل أسباب الطلاق، ووضعت مبادئا عامة لما قد يستجد من مشكلات. ومن تدابير السنة النبوية لمواجهة ظاهرة الطلاق ما سنته من تشريعات من شأنها أن تؤخر أمد الطلاق، لعل الزوجين يراجعان أنفسهما، وحرمت السنة كل الأسباب التي تعاون على إيقاع الطلاق، وأوصت الأزواج بتحمل زوجاتهم، والارتقاء فوق الخلافات. كما أن في السنة من التشريعات الرحيمة ما يساعد على إعادة الحياة الزوجية بعد إيقاع الطلاق.
The spread of divorce is one of the dangerous phenomena that have appeared in our time, which threatens families and societies. The Prophet’s Sunnah has had a great share in addressing the causes of divorce and dealing with its problems. The headmaster in the Prophet’s Sunnah finds that the basic principle in marital life is to prevent divorce, and his hatred is only for the utmost necessity, and with good reason, such as loss of pandemic, bad ten, infertility, etc., and the prophetic Sunnah has dealt with all the causes of divorce, and set general principles for what may arise from problems. Among the measures of the prophetic Sunnah to confront the phenomenon of divorce is the legislation it enacted that would delay the duration of divorce, perhaps the two spouses review themselves, and the Sunnah prohibited all the reasons that helped to divorce, and recommended that husbands tolerate their wives and rise above differences. Also, in the Prophet’s guidance, there are compassionate legislations that help restore marital life after the divorce occurred.
Keywords: ظاهرة الطلاق -- احترام عقد النكاح -- الخلافات الزوجية -- الأحكام الشرعية